Processing in Image Interpolation and Motion Detection - Samuel Ndidi; Victor Iwobi (Journal La Multiapp, 2020)
This article discusses processing in Image Interpolation and Motion Detection. Image or image has become a common thing and has become part of everyday people's life. In a particular interest, image is used as a tool to express various kinds of feelings which for some people are difficult to express through words. Such as explaining a reason, interpretation, illustration, communication, memory, education, evaluation, entertainment, and others. Then the concept of image and its processing is associated with changing and improving the image. Image is a representation, similarity, or imitation of an object or object, for example your photo represents the entity of yourself on camera. X-ray photographs of the chest represent the inside of a person's body, the data in a BMP file represents what it represents.